Inorganic Polymeric Nanocomposites and Membranes - Abe, Akihiro; Dusˇek, Karel; Kobayashi, Shiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
This series presents critical reviews of the present and future trends in polymer and biopolymer science including chemistry, physical chemistry, physics and materials science. It is addressed to all scientists at universities and in industry who wish to keep abreast of advances in the topics covered. Impact Factor Ranking: Always number one in Polymer Science. More information as well as the electronic version of the whole content available at: springerlink.com.
F. Guida-Pietrasanta, B. Boutevin: Polysilakylene or Silarylene Siloxanes Said "Hybrid" Silicones -- O. Becker, G.P. Simon: Epoxy Layered Silicate Nanocomposites -- A.L. Rusanov, D. Likhatchev, P.V. Kostoglodov, K. Müllen, M. Klapper: Proton-Exchanging Electrolyte Membranes Based on Aromatic Condensation Poylmers -- A. Usuki, N. Hasegawa, M. Kato: Polymer-Clay Nanocomposites.
Keywords: Polymers .; Nanotechnology; Inorganic chemistry; Polymer Sciences; Nanotechnology; Inorganic Chemistry